The Effectiveness of the Marriage and Referral Advisory Auxiliary Agency (BP4R) in Minimizing the Divorce of Police Personnel in the North Maluku Regional Police - Endang Husen Bangsa; Jubair Situmorang; Harwis Alimuddin (Tinta Emas Institute, 2025)
Marriage in the lives of members of the Indonesian National Police (Polri) is not merely a legal and emotional bond, but also a component of a social system that influences professional stability and institutional performance. To address domestic issues such as divorce, the National Police established the Marriage, Divorce, and Referral Advisory Auxiliary Agency (BP4R), which aims to provide premarital counseling and mediation. This study adopts an empirical legal (socio-legal) approach, combining a statute-based analysis and a sociological approach. Data collection methods include non-participatory observation, semi-structured interviews, and document analysis, conducted at the North Maluku Regional Police Headquarters from January to March 2024. Data were analyzed using the Miles and Huberman model, involving data reduction, presentation, and conclusion/verification. Findings indicate that BP4R plays a vital role in reducing divorce rates through premarital counseling and mediation. Methods such as lectures, discussions, and individual counseling have helped prepare couples for the realities of married life in the context of police duties. However, its effectiveness remains limited due to short counseling durations, a lack of professional staff (e.g., psychologists), and a perceived formality of the process by some participants. BP4R has had a positive impact on the psychological and administrative readiness of couples prior to marriage, despite the relatively high divorce rate (19.76% in 2024). Strengthening the program’s duration, methods, human resources, and post-session evaluations is essential to enhance the long-term effectiveness and sustainability of BP4R.